Os cursos semipresenciais e o reencontro de jovens e adultos com a educação básica - Farias, Humberto Vieira (2015)
This research was constructed with the intention of analysing the reasons why young people and adults opt to enrol and continue studying in semi-presential courses of Youth and Adult Education in order to complete their basic education. We chose as the location for our research a public school belonging to the Paraiba State school network, which offers such courses for young people and adults at elementary and secondary level. With the theoretical support of such key researchers dedicated to YAE, as Arroyo Beisiegel, Di Pierro, Fávero, Haddad, Ireland, Soares, among a restricted number of researchers who have devoted efforts to reveal some strand of the topic in question and to position the semi-presential courses within the historical context, we set out to recover the origins in the Centres of Suppletive Studies, seeking to understand how such courses work. We certify that this educational proposal, which has already survived for four decades, has always been surrounded by criticism, in addition to suffering from a lack of prestige within educational systems nation-wide, mainly after the last years of the military government. However, official data reveal that these courses still attract a significant number of people and within the methodological proposal adopted in this case study, ‘time’ emerged from the discourse of the subjects as the predominant element of our analysis, leading us to reflect on how some characteristics found in the semi-presential courses can contribute to the construction of a proposal for the modality that respects the times of young people and adults, helping students to keep studying, without having to abdicate other activities often essential to their survival.